2019
DOI: 10.1016/j.jclinane.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial morphine after unintentional dural puncture is not associated with reduced postdural puncture headache in obstetric patients

Abstract: In cases of unintentional dural puncture, exposure to neuraxial morphine for any reason may not be protective against the risk of postdural puncture headache. Although an overall protective effect of neuraxial morphine was not observed in this study, its role in specific subsets of patients remains to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The difference between our results and those of Al-metwalli is surprising, given that spinal and epidural morphine presumably work by similar mechanisms. In addition to the route of morphine administration, the two studies differed in the total dose and timing of administration, the Al-metwalli protocol included a second morphine dose after 24 h. Similar to our findings, in a retrospective analysis of 80 patients exposed to either epidural or intrathecal morphine after an unintentional dural puncture, Brinser et al 25 reported no difference in the incidence of post-dural puncture headache with morphine exposure (48.2%) compared with no exposure (51.8%). After controlling for a history of preeclampsia and mode of delivery the adjusted odds ratio for a post-dural puncture headache was 1.24 (95% CI, 0.13 to 2.33) with neuraxial morphine exposure.…”
Section: Perioperative Medicinesupporting
confidence: 81%
“…The difference between our results and those of Al-metwalli is surprising, given that spinal and epidural morphine presumably work by similar mechanisms. In addition to the route of morphine administration, the two studies differed in the total dose and timing of administration, the Al-metwalli protocol included a second morphine dose after 24 h. Similar to our findings, in a retrospective analysis of 80 patients exposed to either epidural or intrathecal morphine after an unintentional dural puncture, Brinser et al 25 reported no difference in the incidence of post-dural puncture headache with morphine exposure (48.2%) compared with no exposure (51.8%). After controlling for a history of preeclampsia and mode of delivery the adjusted odds ratio for a post-dural puncture headache was 1.24 (95% CI, 0.13 to 2.33) with neuraxial morphine exposure.…”
Section: Perioperative Medicinesupporting
confidence: 81%
“…We found 16 studies detailing labour analgesia through an intrathecal catheter after accidental dural puncture [2, 8, 15, 18, 19, 21–31] (Table 1 and online Supporting Information Table S1). Of these, 13 were retrospective [2, 8, 18, 19, 22, 23, 25–31], two were prospective observational [21, 24] and one was a randomised controlled trial [15]. All of these studies exclusively discussed only the management of accidental dural puncture occurring during labour [2, 15, 18, 19, 21–31], except that of Verstraete et al, which also discussed accidental dural punctures occurring during caesarean sections and fetal surgery [8].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other studies did not prove the protective effect of neuraxial opioids for the prevention of PDPH after ADP with epidural analgesia. [ 21 22 ] Brinser et al . [ 22 ] depended on retrospective medical records.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 22 ] Brinser et al . [ 22 ] depended on retrospective medical records. Moreover, their sample size was small, and the mode of delivery was significantly different between both groups i.e., incidence of vaginal delivery was 50% in the morphine group vs. 2% in the group not administered morphine.…”
Section: Discussionmentioning
confidence: 99%